Public Relations, Mass Media and Informal Education - Demush Bajrami; Teuta Reci; Arburim Iseni (European Scientific Journal, ESJ, 2016)
Nowadays, governments, educational institutions, non-governmental organizations, the private economy and each individual make an effort to integrate the idea of sustainable development in all areas of the educational system. Specific skills and knowledge that we gain as children and teenagers in the family, at school, in training or university will not last for a lifetime. Humanity is programmed to survive. In this context the term ‘programmed’ does not mean the same thing that we use in the computer sciences. Herein, we are dealing with emotional tangle and the continuing struggle to find ourselves. In this way we discovered education as a process. The purpose of practicing this process is that the personal development of an individual can be organized by certain rules. However, the formality enters the function to some extent and we also know that man is inclined to lay in his use of free will. So now we have reached to a new discovery, which is appointed as informal education. This paper, first of all encompasses this form, but also skewed approach to public relations and prospects is also different from those which have been hitherto. First, we will discuss what PR is. Further, we will elaborate education as a process; moreover, we will see how it can be split any further. Hence, history encompasses a factual situation. Lastly, it will be given the interconnection among PR, mass media and informal education.